2014
DOI: 10.3389/fphys.2014.00440
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid attenuates cigarette smoke-induced lung inflammation by inhibiting ROS-sensitive inflammatory signaling

Abstract: Cigarette smoking causes chronic lung inflammation that is mainly regulated by redox-sensitive pathways. Our previous studies have demonstrated that cigarette smoke (CS) activates reactive oxygen species (ROS)-sensitive mitogen-activated protein kinases (MAPKs)/nuclear factor-κB (NF-κB) signaling resulting in induction of lung inflammation. Eicosapentaenoic acid (EPA), a major type of omega-3 polyunsaturated fatty acid, is present in significant amounts in marine-based fish and fish oil. EPA has been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…It is interesting to note that many studies have linked the anti-inflammatory effects of compounds contained in microalgae with the inhibition of the NF-κB signaling pathway. A study on human bronchial epithelial cells also showed that EPA, by inhibiting MAPKs/NF-κB signaling, inhibits IL-8 induced by cigarette smoke extracts [85]. In another study, fucoxanthin was reported to reduce pro-inflammatory mediator levels via the inhibition of NF-κB pathway activation in murine macrophages [69].…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that many studies have linked the anti-inflammatory effects of compounds contained in microalgae with the inhibition of the NF-κB signaling pathway. A study on human bronchial epithelial cells also showed that EPA, by inhibiting MAPKs/NF-κB signaling, inhibits IL-8 induced by cigarette smoke extracts [85]. In another study, fucoxanthin was reported to reduce pro-inflammatory mediator levels via the inhibition of NF-κB pathway activation in murine macrophages [69].…”
Section: Discussionmentioning
confidence: 97%
“…The lung inflammatory score was categorized according to the sum of the scores for the infiltration cell numbers and damage level, including the thickening of alveolar walls and epithelium. This grading method has been used in our previous studies (Liu et al, 2014; Lin et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we hypothesized that M-CS could induce more severe lung inflammation than Non-M-CS could via the additional action of menthol on TRPM8. In testing this hypothesis, we employed a murine model of CS exposure (Tang et al, 2011; Liu et al, 2014; Wu et al, 2014) to compare various indices of lung inflammation and activation of MAPKs in lung tissues induced by subchronic exposure to Non-M-CS and M-CS. We used a selective TRPM8 antagonist ( N -(3-aminopropyl)-2-{[(3-methylphenyl) methyl]oxy}- N -(2-thienylmethyl) benzamide; AMTB) (Journigan and Zaveri, 2013) as the intervention to assess the role of TRPM8 in these responses.…”
Section: Introductionmentioning
confidence: 99%
“…Paeonol (2’-hydroxy-4’-methoxyacetophenone, C 9 H 10 O 3 ) is a phenolic acid compound extracted from the famous Cortex Moutan, which has been widely employed in traditional Chinese medicine (TCM). It is well established that Paeonol exerts anti-inflammatory activities to relieve ovalbumin-induced asthma [ 32 ] and cigarette smoke-induced lung inflammation [ 33 ] in a murine model, free-radical scavenging properties to prevent against neurotoxicity in vitro [ 34 , 35 ], and anti-tumor effects in culture cells [ 36 , 37 ]. Paeonol administration may reduce ischemia-reperfusion injured cerebral infarction [ 38 ] and ameliorate cognitive deficits in streptozotocin-induced diabetic rats [ 39 ].…”
Section: Introductionmentioning
confidence: 99%